2020
DOI: 10.1111/pce.13929
|View full text |Cite
|
Sign up to set email alerts
|

Implications of ionizing radiation on pollen performance in comparison with diverse models of polar cell growth

Abstract: Research concerning the effects of ionizing radiation (IR) on plant systems is essential for numerous aspects of human society, as for instance, in terms of agriculture and plant breeding, but additionally for elucidating consequences of radioactive contamination of the ecosphere. This comprehensive survey analyses effects of x‐ and γ‐irradiation on male gametophytes comprising primarily in vitro but also in vivo data of diverse plant species. The IR‐dose range for pollen performance was compiled and 50% inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(45 citation statements)
references
References 234 publications
3
42
0
Order By: Relevance
“…Concerning collective plant microgametophytes the mean value of 50% inhibition doses (ID 50 ) for gammaradiation amounts to significantly more than 1000 Gy. Whereas the mean ID 50 of plant sporophytes is substantially below 100 Gy [15]. Also the IR-tolerance of fungal hyphae is considerably higher than that of plant sporophytes.…”
Section: Actin-related Ir-sensitive Yeast Deletion Mutantsmentioning
confidence: 87%
See 3 more Smart Citations
“…Concerning collective plant microgametophytes the mean value of 50% inhibition doses (ID 50 ) for gammaradiation amounts to significantly more than 1000 Gy. Whereas the mean ID 50 of plant sporophytes is substantially below 100 Gy [15]. Also the IR-tolerance of fungal hyphae is considerably higher than that of plant sporophytes.…”
Section: Actin-related Ir-sensitive Yeast Deletion Mutantsmentioning
confidence: 87%
“…In the latter case, polarized growing hyphae of filamentous fungi generate large mycelial structures and sporocarps (fruitbodies). Members of the multifaceted taxon fungi thrive in diverse habitats, yet their tolerance of ionizing radiation is in general very high, which is similar to the extreme IR-resistance of pollen performance [15]. Concerning collective plant microgametophytes the mean value of 50% inhibition doses (ID 50 ) for gammaradiation amounts to significantly more than 1000 Gy.…”
Section: Actin-related Ir-sensitive Yeast Deletion Mutantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the effects of irradiation doses on in vitro pollen tube length may differ among plant species in a dosedependent manner. Additionally, Stephan (2021) indicated that ionization radiation affects pollen tube growth and nuclear function. Ionization radiation causes dramatic impairment of the genome entity, but its effects on polar growth are minor.…”
Section: Discussionmentioning
confidence: 99%